In-service teacher training in Portugal: objectives, organization and impact on teacher's career - Ferreira, Olga (2014)
This paper presents a short overview of teacher´s training as considered by the Portuguese legislation: (i) initial teacher education (ITE), (ii) specialized training and (iii) in-service teacher training. A particular emphasis will be given to in-service teacher training. Nowadays, ITE corresponds to level 7 of the European Qualifications Framework (master degree). It is a career-long professional development, where research-based and in context practice are important features. Specialized training is intended to provide qualification in complementary educational functions, such as special education, school administration and inspection activities, socio-cultural animation and basic education for adults. In-service training or continuous training allows teachers to complement, deepen and update their knowledge and professional competences. Its accreditation, in what concerns involved institutions, training actions and evaluation process is centralized in the “Conselho Científico-Pedagógico da Formação Contínua” (Scientific and Pedagogical Council of in-service training) and has a direct impact in teacher’s careers, being one of the factors considered to access mobility and progression.